Leaf gas exchange and fruit yield in sweet orange trees as affected by citrus variegated chlorosis and environmental conditions - Habermann, Gustavo [UNESP]; Rodrigues, Joao Domingos [UNESP] (Elsevier B.V., 2009)
Citrus variegated chlorosis (CVC) is a disease caused by the bacterium Xylella fastidiosa. The most productive areas for citrus in Brazil are the northwestern and the northern regions of the São Paulo state, where CVC incidence is more severe. Additionally, these areas have the highest temperatures as well as significant vapor pressure deficits (VPD) and seasonal droughts. Environmental stresses are known to affect CVC-infected plants under semi-controlled conditions, but it is unclear whether similar effects occur in the field. The objective of this work was to evaluate the CVC leaf symptoms and environmental influences on fruit yield and size, and physiological parameters of healthy and CVC-affected plants (including both non-symptomatic and symptomatic leaves) in the morning and afternoon during the wet and dry seasons of 2003 in the southern, central and northern regions of the São Paulo state, Brazil. Increased VPD caused the stomatal conductance (gs) and CO(2) assimilation rates (A) to drop in healthy plants, but diseased plants had low VPD influences on gs, especially closer to the northern region and in leaves that were more symptomatic, confirming that diseased plants do not respond to changes in environmental VPD, corroborating several results reported in the literature. Although symptomatic northern leaves exhibited low stomatal apertures, the northern region had the highest air temperatures and VPDs, increasing the water loss in these plants, suggesting that towards the northern region plants face greater atmospheric and soil water stress. The fruit size of diseased plants diminished towards the north, while the fruit size of healthy plants must have been influenced by the tree fruit load. We suggest that CVC-affected plants suffer greater physiological damage if grown under environmental constraint, such as that found in the northern region of the São Paulo state. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrus sinensis; Photosynthesis; Seasonal effects; Xylella fastidiosa